I can draw people - Gibson, Ray.; Watts, Fiona (Tulsa, Okla. : EDC Pub., 2000)
Shows how to draw people including a workman, an angel, a soccer player, an astronaut, a parachutist, and an ice skater.
Workman -- Angel -- Giant -- Pirate -- Queen -- Ballerina -- Soccer player -- Scuba diver -- Astronaut -- Parachutist -- Skier -- Ice skater -- Cowboy -- Faces -- Horse and rider.
Keywords: Drawing -- Technique; Human figure in art; Drawing -- Technique -- Juvenile literature; Human figure in art -- Juvenile literature